Produção de novilhos em pastagem de inverno com diferentes intensidades de pastejo e adubação nitrogenada em integração lavoura-pecuária - Barriga, Pablo Antonio Beltran (2019)
The use of management strategies, such as adjustment of grazing intensity and nitrogen fertilization, are fundamental for the success of the production of steers in integrated crop- livestock systems (ICLS). The aim of this work was to evaluate the effects of grazing intensity and nitrogen fertilization on the production and nutritional composition of forage, performance, ingestive behavior and patterns of movement of the animals, in ICLS. The experiment was carried out in an area of 14 ha, ILP system implemented in 2012 in Abelardo Luz - SC. The experimental design was in randomized blocks with three replications, distributed in a factorial scheme (2x2). The following factors were studied: Sward height: high (HH - 25 cm) and low (LH -10 cm), and the second factor was the N fertilization season in the system: N applied to pasture (NP) and N applied to grain crops (NG). Both applications corresponded to the dose of 200 kg of N ha-1. The height of the pasture was regulated by means of continuous stocking and variable stocking rate of Charolais x Nellore beef cattle. Before the entry of the animals, pastures fertilized with N (NP) showed higher grass height, forage mass, forage accumulation, population density of tillers, radiation interception, forage density, leaf mass, stalk mass and area index were larger. With nitrogen fertilization of 200 kg ha-1 in the pasture, it is possible to manage the 'Winter Star' ryegrass pasture with an average height of 12.2 cm. The forage mass was higher for pastures managed with 25 cm of height and application of N in the pasture (NP). At the end of grazing, nitrogen fertilization of pasture (NP) resulted in higher crude protein content, lower neutral detergent fiber and acid detergent fiber at the end of grazing. With advance of the grazing period and ryegrass phenology for the final period, it was observed decrease of the crude protein and increase of neutral and acid detergent fiber. The mean daily gain did not show differences between treatments. The average gain per area, the animal load and the stocking rate were higher in pastures managed at 10 cm in height and nitrogen fertilization in the pasture (NP). The thickness of subcutaneous fat at the end of the evaluation period in all treatments was greater than 3.0 mm. The animals intensified the foraging and seizure processes in pastures managed at 10 cm and nitrogen applied to the pasture, due to the lower mass and forage supply. In LHBP, there was an increase in the speed of ingestion, shorter stay of the animals in the food season, fewer mouths per season and visiting more stations. At the end of the grazing period, with lower forage mass, the animal walked less between food stations, increasing the total number of bites and modifying their behavior patterns according to the pasture phenology.